Size effect investigation using piezo-actuated micro-compression machine - Shukri Abdul Jalil (2014)
Increasing demands for micro-sized metal parts call for a new type of micro manufacturing technique. Micro-forming are increasingly being suggested as it is more feasible for mass production with almost zero material loss as well as good finished products. Micro-forming is macro-forming scaled down however the involved parameters are not necessarily scaled down proportionally or may even not be scaled down at all. This is due to size effect which posed a challenge to the development of micro-forming techniques as the known macro-forming techniques cannot be directly applied to micro-forming. To better understand the micro materials’ behavior, a piezo-actuated micro-compression system which was built in-house was used to perform compression tests to give the different stress-strain curves at different conditions. Since the machine is considerably newly developed, there are still much to be improved on as its effectiveness in performing the compression tests are limited. These improvements can only be determined with increased machine usage, as such issues with the machines can be identified and improved on. Aluminium and Titanium were the materials chosen for this study due their various micro applications. Samples of three different sizes were prepared from both materials, diameter 2 mm by 2.5 mm height , diameter 1 mm by 1.25 mm height and diameter 0.5 mm by 0.625 mm height. For each sample size, three different strain rates were used for this project. There is a significant size effect on the flow stress which generally increases with decreasing sample size. The same can also be said for the effect of the different strain rates on the resultant flow stress which increases with increasing strain rate. There is also a trend on the way these materials go through plastic deformation with different strain rates and sample size.